Patient-Centered Outcomes in a Randomized Trial Investigating a Multimodal Prevention Program After Transient Ischemic Attack or Minor Stroke: The INSPiRE-TMS Trial. Issue 9 (15th June 2022) - Ihl, Thomas; Ahmadi, Michael; Laumeier, Inga; Steinicke, Maureen; Ferse, Caroline; Klyscz, Philipp; Endres, Matthias; Hastrup, Sidsel; Poppert, Holger; Palm, Frederick; Kandil, Farid I.; Weber, Joachim E.; et al.
Abstract : Background: The INSPiRE-TMS trial (Intensified Secondary Prevention Intending a Reduction of Recurrent Events in Transient Ischemic Attack and Minor Stroke Patients) investigated effects of a multicomponent support program in patients with nondisabling stroke or transient ischemic attack. Although secondary prevention targets were achieved more frequently in the intensified care group, no significant differences were seen in rates of recurrent major vascular events. Here, we present the effects on prespecified patient-centered outcomes. Methods: In a multicenter trial, we randomized patients with modifiable risk factors either to the intensified or conventional care alone program. Intensified care was provided by stroke specialists and used feedback and motivational interviewing strategies (≥8 outpatient visits over 2 years) aiming to improve adherence to secondary prevention targets. We measured physical fitness, disability, cognitive function and health-related quality of life by stair-climbing test, modified Rankin Scale, Montreal Cognitive Assessment, and European Quality of Life 5 Dimension 3 Level during the first 3 years of follow-up. Results: Of 2072 patients (mean age: 67.4years, 34% female) assessed for the primary outcome, patient-centered outcomes were collected in 1, 771 patients (877 intensified versus 894 conventional care group). Physical fitness improved more in the intensified care group (mean between-group difference in power (Watt): 24.5 after 1 year (95% CI, 5.5–43.5); 36.1 after 2 years (95% CI, 13.1–59.7) and 29.6 (95% CI, 2.0–57.3 after 3 years). At 1 year, there was a significant shift in ordinal regression analysis of modified Rankin Scale in favor of the intensified care group (common odds ratio, 1.23 [95% CI, 1.03–1.47]) but not after 2 (odds ratio, 1.17 [95% CI, 0.96–1.41]) or 3 years (odds ratio, 1.16 [95% CI, 0.95–1.43]) of follow-up. However, Montreal Cognitive Assessment and European Quality of Life 5 Dimension scores showed no improvement in the intensified intervention arm after 1, 2, or 3 years of follow-up. Conclusions: Patients of the intensified care program group had slightly better results for physical fitness and modified Rankin Scale after 1 year, but none of the other patient-centered outcomes was significantly improved. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01586702.